Prediction of NPK doses based on targeted fruit sugar content in Cucumis melo L. ‘Cantaloupe’ using a simple regression method - Wibawa, Rangga; Mubarok, Syariful; Kusumiyati, Kusumiyati; Wicaksono, Fiky Yulianto; Ruminta, Ruminta; Budiarto, Rahmat; Putri, Dina; Varinto, Irvan; Rizki, Muhammad; Maolana, Adrian; Nisa, Kahirun; Giyarto, Gunes (Kultivasi, 2024)
The fruit sweetness is the main target in melon plant production. The highest criterion of sweetness is excellent, with 16% of total sugar content. Modification of essential plant nutrients is the alternative to reach that category. So, this study aims to obtain optimum NPK doses using a simple regression method. The experiment was conducted in a greenhouse with a soilless culture hydroponic system from August until November 2023 using a completely randomized design (CRD) with five treatments and four replications. The parameters included leaf area, plant dry matter, leaf nutrient uptake, fruit weight, and fruit sugar content. Pearson correlation analysis showed that the total sugar content in fruit has a significantly positive correlation with potassium in NPK fertilizer treatments such as K2O dose and K2O uptake at 7 WAP, i.e., 0.932 and 0.973, respectively. According to the regression model y = -50.7 + 1.079 N + 0.251 P2O5 + 0.528 K2O, the NPK formula fertilizer containing 31.56 g N, 23.99 g P2O5, and 50.42 g K2O can be used by grower to produce excellent fruit sugar content.